Reliability Evaluation Model of Component‐Based Software Based on Complex Network Theory. (16th June 2016) - Li, Kewen; Liu, Lu; Zhai, Jiannan; Kosgoftaar, Taghi M.; Shao, Mingwen; Liu, Wenying
Abstract : Component‐based software development is now a widely used software development technique. In this paper, we propose a reliability evaluation model used to evaluate component‐based software systems, focusing on analyzing the effects of different components on software reliability. Our model utilizes the complex network theory based on the state‐based evaluation approach. First, a detailed analysis is made to identify the components used in a software system. Next, the most influential node discovery algorithm in complex network theory is used to calculate the impact factor of each component. Finally, the reliability of the software system is evaluated based on the impact factors. Results show that the proposed model achieves better accuracy compared with conventional models by using the internal structure of the software system during evaluation. Copyright © 2016 John Wiley & Sons, Ltd.